Carcass wrote:
\(−7x − 2y = −13\), and \(x − 2y = 11\). The variable y =
A -3
B -4
C 3
D 4
E 7
Let's label the two equations as follows:
(1) \(x − 2y = 11\)
(2) \(−7x − 2y = −13\)
To eliminate the y's, we can subtract equation (2) from equation (1) to get: \((x − 2y) - (-7x - 2y) = 11 - (-13)\)
Simplify: \(8x = 24\)
Solve: \(x = 3\)
To find the corresponding value of y, plug \(x = 3\) into equation (1) to get: \(3 − 2y = 11\)
Subtract 3 from both sides of the equation: \(−2y = 8\)
Solve: \(y = \frac{8}{-2} = -4\)
Answer: B